PHYTOCHEMICAL PROPRETIES OF PUNICA GRANATUM AND THEIR ANTIOXYDANT EFFECTS ON FABA BEAN SEEDLINGS UNDER METALLIC STRESS - Cheddadi Bouchra; Kiassa Nour (My University, 2025)
This research focuses on examining the biological characteristics of pomegranate (Punica granatum.L), particularly its antioxidant, anti-inflammatory, and cytoprotective properties. By studying two local Algerian varieties from the province of Souk Ahras (Ouled-Dris), Doux de Koléa and Doux de Messaad, we isolated the bioactive compounds from the peels using different solvents (methanol, butanol, chloroform), and then determined the amount of polyphenols, flavonoids, and tannins they contain. The methanolic solutions were distinguished by a high content of phenolic compounds: 290.73 mg EAG/g for polyphenols (EMV2), 2.3349 mg QE/g for flavonoids (EMV2), and 17.64 mg EC/g for tannins (EMV1). These extracts also demonstrated remarkable antioxidant activity, with an IC₅₀ value of 6.01 ± 1.30 µg/mL for EMV1, which even exceeds the standard for ascorbic acid . From a cytogenetic perspective, the extracts demonstrated a modest protective effect. However, in the presence of cadmium, they sometimes exacerbated chromosomal abnormalities (micronuclei, macronuclei), suggesting a potential interaction between antioxidant compounds and heavy metals. This study highlights the great curative potential of pomegranate, while emphasizing the importance of further investigating its biological effects, particularly in situations of oxidative stress. ---------------------------------------------------------------------------------------------------------------------------------- يركز هذا البحث على دراسة الخصائص البيولوجية لثمار الرمان(Punicagranatum.L)، وخاصة آثاره المضادة للأكسدة، والمضادة للالتهاب، والواقية للخلايا. من خلال دراسة صنفين محليين من ولاية سوق أهراس الجزائرية، وهما "الحلو القولي" و"الحلو المسعد"، قمنا بعزل المركبات النشطة بيولوجيًا من القشور باستخدام مذيبات مختلفة (الميثانول، البوتانول، الكلوروفورم)، ثم قمنا بتحديد كميات البوليفينولات، الفلافونويدات، والتانينات الموجودة فيها. تميزت المحاليل الميثانولية بمحتواها العالي من المركبات الفينولية: 290.73 مغ ما يعادل حمض الغاليك/غ للبوليفينولات (EMV2)، 2.3349 مغ ما يعادل الكيرسيتين/غ للفلافونويدات (EMV2)، و17.64 مغ ما يعادل التانينات/غ التانينات (EMV1). كما أظهرت هذه المستخلصات نشاطًا مضادًا للأكسدة ملحوظًا، بقيمة IC₅₀تبلغ 6.01 ± 1.30 ميكروغرام/مل لـ EMV1، متجاوزة حتى معيار حمض الأسكوربيك. من الناحية السيتوجينية، أظهرت المستخلصات تأثيرًا وقائيًا محدودًا. ومع ذلك، في وجود الكادميوم (عامل مسبب للتلف الجيني)، زادت في بعض الأحيان من التشوهات الكروموسومية (النوى الصغيرة، النوى الكبيرة)، مما يشير إلى تفاعل محتمل بين المركبات المضادة للأكسدة والمعادن الثقيلة. تؤكد هذه الدراسة على الإمكانات العلاجية الكبيرة للرمان، مع التأكيد على أهمية تعميق فهم آثاره البيولوجية، خاصة في حالات الإجهاد التأكسدي. ------------------------------------------------------------------------------------------------------------------------------------------ Ce travail de recherche se concentre sur l'examen des caractéristiques biologiques de la grenade (Punicagranatum), en particulier ses actions antioxydantes, anti-inflammatoires et cytoprotectrices. En étudiant deux variétés locales algériennes de la wilaya de Souk ahras (Ouled-Dris), Doux de Koléa et Doux de Messaad, nous avons isolé les composés bioactifs des écorces en utilisant différents solvants (méthanol, butanol, chloroforme), puis déterminé la quantité de polyphénols, flavonoïdes et tanins qu'elles contiennent. Les solutions méthanoliques se distinguent par une teneur élevée en composés phénoliques : 290,73 mg EAG/g pour les polyphénols (EMV2), 2,3349 mg QE/g pour les flavonoïdes (EMV2), et 17,64 mg EC/g pour les tanins (EMV1). Ces extraits ont aussi démontré une activité antioxydante remarquable, avec une valeur IC50 de 6,01 ± 1,30 µg/mL pour EMV1, qui dépasse même la norme de l'acide ascorbique. D'un point de vue cytogénétique, les extraits ont montré un effet protecteur modeste. Cependant, en présence de cadmium (un agent génotoxique), ils ont parfois exacerbé les anomalies chromosomiques (micronoyaux, macronoyaux), suggérant une potentielle interaction entre les composés antioxydants et les métaux lourds. Cette étude met l'accent sur le grand potentiel curatif de la grenade, tout en insistant sur l'importance d'approfondir ses effets biologiques, en particulier dans des situations de stress oxydatif.
Keywords: pomegranate; flavonoids; and tannins; polyphenols; chromosomic aberration الرمان ،الفلافونويدات، والتانينات ،البوليفينولات، التشوهات الجينية. La grenade; flavonoïdes et tanins; polyphénols; les anomalies chromosomiques